The allure of the ancient : receptions of the ancient Middle East, ca. 1600-1800 - Geoga, Margaret; Geoga, Margaret; Steele, John M.; Steele, John M. (Intersections, 2022)
"The Allure of the Ancient investigates how the ancient Middle East was imagined and appropriated for artistic, scholarly, and political purposes in the seventeenth and eighteenth centuries. Bringing together scholars of the ancient and early modern worlds, the volume approaches reception history from an interdisciplinary perspective, asking how early modern artists and scholars interpreted ancient Middle Eastern civilizations-such as Egypt, Babylonia, and Persia-and how their interpretations were shaped by early modern contexts and concerns. The volume's chapters cross disciplinary boundaries in their explorations of art, philosophy, science, and literature, as well as geographical boundaries, spanning from Europe to the Caribbean to Latin America"--